THE ETHNIC ART LIFE OF THE UKRAINIANS OF KOLOMYYA TOWN DURING THE PERIOD OF THE WEST UKRAINIAN PEOPLE’S REPUBLIC (1918-1919) - Korol’ko, A. Z. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The ethnic art life of the Ukrainians in Kolomyya town during the national liberation movements of the West Ukrainians in 1918-1919 is characterized in the given article. The author has characterized the activity of local Ivan Tobilevych Ukrainian public theatre, other art establishments that played on tour in the main city of Pokuttya; highlighted the activity of cultural society «Moloda Gromada» («The Young Community»).